Preliminary Draft Report on Pilot Project for Western Region U.P. (1978-82) - Planning Commission (Planning Commission, 1978)
The Government has announced the broad features of its economic policy and has also outlined the details of its dynamics. the whole policy centres round the three essential themes. They are as under:- Decentralisation in the process of planning; Elevation of agriculture to the dominant position; Mass Oriented industrialisation.
Uttar Pradesh